Solid waste disposal system: incineration against landfill system / Siti Rahayu Ahmad - Ahmad, Siti Rahayu (2003)
Population growth, rising standards of living, and industrialization all have contributed to increased solid waste generation in both industrialized and developing countries. Solid wastes pose significant threats to public health and the environment if they are not stored, collected, and disposed of properly The most serious effects of improper solid waste management include air pollution, contamination of water supplies, and the spread of human disease. This dissertation was carried out to identify the process of incineration and landfill system as solid waste disposal system and to determine the merits between incineration and landfill. As the process is technically different, the aim of using these system is same as to control the increasing of amount of solid wastes. Both of the system have their advantages and disadvantages that can be found through the chapters in this dissertation. These problems suggest the need for government policy-makers to explore pollution prevention options and to consider regulatory and enforcement strategies to minimize the harmful environmental impacts of improper solid waste management practices, especially those used in landfilling, the main method of waste disposal in the world and incineration as an alternative solid waste disposal system.